STRESS DISTRIBUTION CAUSED BY CO-PHASE LOCALLY SPATIALLY CURVED LAYERS IN AN INFINITE ELASTIC BODY UNDER BI-AXIAL COMPRESSION - Tekercioglu, Ramazan (VINCA INST NUCLEAR SCI, 2019)
In the present paper, the stress distribution is studied in an infinite elastic body, reinforced by an arbitrary number of non-intersecting co-phase locally spatially curved filler layers under bi-axial compression is studied. It is assumed that this system is loaded at infinity with uniformly distributed normal forces with intensity p(1)(p(3)) acting in the direction which is parallel to the layers' location planes. It is required to determine the self-equilibrated stresses within, caused by the spatially local curving of the layers. The corresponding boundary and contact value problem is formulated within the scope of geometrically non-linear exact 3-D equations of the theory of elasticity by utilizing of the piece-wise homogeneous body model. The solution the formulated problem is represented with the series form of the small parameter which characterizes the degree of the aforementioned local curving. The boundary-value problems for the zeroth and the first approximations of these series are determined with the use of the exponential double Fourier transform. The original of the sought values is determined numerically. Consequently, in the present investigation, the effect of the local curving on the considered interface stress distribution is taken into account within the framework of the geometrical non-linear statement. The numerical results related to the considered interface stress distribution and to the influence of the problem parameters on this distribution are given and discussed.
Keywords: stress distribution; local curving; double Fourier transform; geometrical Non-linearity; UNDULATION INSTABILITY; THIN-FILMS; Thermodynamics